Association of the multi-biomarker disease activity score with joint destruction in patients with rheumatoid arthritis receiving tumor necrosis factor-alpha inhibitor treatment in clinical practice. Issue 6 (1st November 2016) - Hirata, Shintaro; Li, Wanying; Kubo, Satoshi; Fukuyo, Shunsuke; Mizuno, Yasushi; Hanami, Kentaro; Sawamukai, Norifumi; Yamaoka, Kunihiro; Saito, Kazuyoshi; Defranoux, Nadine A.; Tanaka, Yoshiya
Abstract: Objective : Evaluate the association between the multi-biomarker disease activity (MBDA) score and radiographic progression in patients with rheumatoid arthritis (RA) treated with tumor necrosis factor (TNF)-α inhibitors. Methods : Change (Δ) in modified total Sharp score (mTSS) over 52 weeks and disease activity scores were examined retrospectively by Spearman's rank correlation coefficient in patients ( N = 83) with RA initiating TNF-inhibitor treatment. Relative risk (RR) of ΔmTSS >0.5 for low MBDA score and 28-joint count disease activity score (DAS28) categories and associations between ΔmTSS and MBDA score categories conditional on DAS28 categories were assessed. Results : At 52 weeks, 34% of patients had ΔmTSS >0.5 and 12% had ΔmTSS >3. Strongest correlations were observed between ΔmTSS and MBDA score ( r = 0.47) or DAS28 ( r = 0.42) at Week 24 and for area under the curve at Week 52 (MBDA score: r = 0.44, DAS28: r = 0.41), all p < 0.001. At Week 24, RR of ΔmTSS >0.5 for moderate/high MBDA score (≥30) or DAS28 (>3.2) were 6.6 ( p < 0.001) and 2.7 ( p = 0.005), respectively. Low DAS28 had greater risk of ΔmTSS >0.5 at 52 weeks when MBDA score was ≥30 ( p < 0.05). Conclusion : Higher MBDA score or DAS28 at Week 24 was associated with greater radiographic progression over 52 weeks of TNF-inhibitor treatment. MBDA score improved risk discrimination for radiographic progression within DAS28 categories.